Shattered Sky: Warriors: a Vision of Shadows #3 Warriors: a Vision of Shadows #3 - Hunter, Erin (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2017)
After the ShadowClan falls, a group of rogues and their cruel leader are ruling the pine forest, and the Clan's only hope is to find the lost SkyClan and fulfill the StarClan's prophecy.
new kids book 2023 spring.
Keywords: Fantasy; Cats -- Fiction; Prophecies -- Fiction; Cats -- Fiction; Prophecies -- Fiction; Fantasy fiction